The Influence of the School Environment on the Motivation of PIP Recipients to Pursue Higher Education - Rina Rifana Nurfaida; Dwi Hastuti; Irni Rahmayani Johan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
Higher education plays a strategic role in improving the quality of human resources and promoting social mobility. Nevertheless, participation in higher education among students from low-income families in Indonesia remains relatively low, even when financial assistance such as the Program Indonesia Pintar (PIP) is available. This condition suggests that nonfinancial factors also shape students' decisions to continue their studies. The present study aims to examine the effect of the school environment on PIP recipients' motivation to continue their education to higher levels. A quantitative explanatory approach with a cross-sectional design was employed. The sample size was determined using the Slovin formula and resulted in a minimum of 395 respondents, while the actual data collected reached 423 PIP recipients from public senior high schools. Respondents were drawn through accidental sampling, with 416 students originating from 21 subdistricts across Garut Regency and 7 students from outside the regency. The school environment was measured through learning facilities, teacher support, and peer interaction, while motivation was measured through intrinsic, extrinsic, and amotivation dimensions. Data were analyzed using simple linear regression with SPSS version 27. The results show that the school environment has a positive and significant effect on the motivation to continue higher education, with a regression coefficient of 0.157, F value of 92.156, and significance level below 0.001. The school environment explains 18.0 percent of the variance in motivation. These findings confirm that nonfinancial factors within the school setting substantively shape the educational aspirations of disadvantaged students